OPTIMISATION OF THE PERFORMANCE OF THE ATM NETWORK IN EUROPE - Luppo, Alexandr; Argunov, Gennadiy; Gorlenko, Nikita; Chaika, Vladyslav (Proceedings of National Aviation University (archive), 2014)
This article is devoted to the consideration of issues of the organization of the European ATM network, and the functional tasks that are under the responsibility of the body that is integrating them – Network Manager.